Cervical Ligamentum Flavum Cyst Causing Myelopathy: A Case Report - Thomas J Kishen; Prabhakar Sekar (Journal of Orthopedics and Joint Surgery)
Aims and background: Symptomatic ligamentum flavum cysts in the cervical spine are an uncommon entity and can potentially cause neural compression, leading to radiculopathy and myelopathy. In this report, we discuss the clinical presentation, imaging findings, and management of a cervical ligamentum flavum cyst causing myelopathy in a 68-year-old gentleman. Case description: A 68-year-old gentleman presented with progressive paresthesia and weakness of both upper limbs of 6 months duration, along with clumsiness of both hands and difficulty in walking. Magnetic resonance imaging (MRI) scan of the cervical spine showed a ventral midline ligamentum flavum causing cord compression and myelomalacia along with bilateral C3-C4 facet arthritis. The patient underwent a C3-C5 limited laminectomy, undercutting of the superior border of C6 lamina and C3-C6 lateral mass screw-based instrumented fusion with locally harvested autograft. At the 3-month follow-up, the gait, motor power, and sensations in all four limbs had returned to normal. Conclusion: Ligamentum flavum cysts in the subaxial cervical spine are the result of spinal degeneration and have the potential to cause myelopathy. Surgical excision of the cyst and neural decompression with or without fusion is the treatment of choice for symptomatic cysts. Clinical significance: Cervical ligamentum flavum cyst is an uncommon entity and can potentially cause myelopathy and/or radiculopathy. It is imperative to recognize this entity on imaging and correlate it with the symptoms. Surgical excision of the cyst, with or without fusion, is the treatment of choice.